2009
DOI: 10.1590/s0100-736x2009000800012
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos clínicos, morfológicos e imuno-histoquímicos da pitiose gastrintestinal canina

Abstract: Pesq. Vet. Bras. 29(8):673-679, agosto 2009 RESUMO.-Através de um estudo retrospectivo dos casos de biópsias e necropsias de cães recebidos no Laboratório de Patologia Veterinária da Universidade Federal de Santa Maria, constatou-se a ocorrência de dois casos confirmados e de quatro casos suspeitos de pitiose gastrintestinal canina. Os dois casos diagnosticados e publicados tiveram a etiologia confirmada através da cultura e indução de zoosporogênese ou por nested-PCR. Neste estudo utilizou-se a técnica de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1
33

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 25 publications
1
9
1
33
Order By: Relevance
“…The confirmation was made by immunohistochemistry, which is an effective and advantageous method, when unable to be performed culture or isolation of the agent (Trost et al 2009). The disease occurred mainly in young dogs, regardless the breed and sex similar to that described by Fischer et al (1994), differently from what was reported by Trost et al (2009), where there was a higher occurrence in large sized males.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The confirmation was made by immunohistochemistry, which is an effective and advantageous method, when unable to be performed culture or isolation of the agent (Trost et al 2009). The disease occurred mainly in young dogs, regardless the breed and sex similar to that described by Fischer et al (1994), differently from what was reported by Trost et al (2009), where there was a higher occurrence in large sized males.…”
Section: Discussionmentioning
confidence: 99%
“…The confirmation was made by immunohistochemistry, which is an effective and advantageous method, when unable to be performed culture or isolation of the agent (Trost et al 2009). The disease occurred mainly in young dogs, regardless the breed and sex similar to that described by Fischer et al (1994), differently from what was reported by Trost et al (2009), where there was a higher occurrence in large sized males. Pythiosis traditionally found in tropical, subtropical and temperate regions (Gaastra et al 2010), the five case studies occurred in the semiarid of Northeast Brazil that is characterized by having the dry and hot climate and the scarcity and irregular rainfall, however in four of five cases in this study the animals have contact with wetlands, which constitutes a risk factor for the occurrence of the disease, since preferably the agent inhabits aquatic environments which induces zoospore formation (Supabandhu et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O diagnóstico foi confirmado pela análise imuno-histoquímica utilizando anticorpo anti-Pythium insidiosum segundo técnica descrita por Trost et al (2009).…”
Section: Relato Do Casounclassified
“…SEG should be considered in the differential diagnosis of tumor-like lesions that present eosinophil infiltration in the stomach wall including gastric pythiosis (TROST et al, 2009) and gastric mast cell tumors. The diagnosis of gastric pythiosis was excluded because no fungal structures were observed upon GMS staining.…”
Section: A Gastrite Eosinofílica Esquirrosa (Gee) émentioning
confidence: 99%